Evaluación de la deformación de dos siliconas para prótesis faciales, influencia de la pigmentación y desinfección química - Coelho, Marcelo Goiato [UNESP]; Do Prado, Paula Ribeiro [UNESP]; Rocha, Aline Úrsula Fernandes [UNESP]; Alves, Aldiéris Pesqueira [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Dos Santo, Daniela Micheline [UNESP]; Filho, Humberto Gennari [UNESP] (My University, 2010)
The purpose of present study was to analyze the effect of pigmentation and chemical disinfection on the initial and the permanent deformation of two silicones (Silved Selant and Brascoved) for facial prosthesis. Initial and permanent deformation tests samples (20 mm × 12.5 mm) were made following the manufacturer's instructions. For each silicone (n= 40), ten samples were used for pigmentation with make up power, ten with iron oxide, ten with ceramics power and tem were tested without pigmentation. Five samples of each group were submitted to chemical disinfection using a 2 % Chlorhexidine spray. All samples were immersed in physiological saline and stored in an oven at 35 ° ± 1 °C. After 90 days, the samples were submitted to initial and permanent deformation tests using a dial indicator. For both properties, data were analyzed by Tukey's test (a= 0.05). The results showed that all the materials had initial and permanent deformation regardless of pigmentation and chemical disinfection. The groups were used for pigmentation with iron oxide showed less initial and permanent deformation when were submitted to the chemical disinfection regardless the silicone used.
Assessment of initial and the permanent deformation of two silicones (Silved Selant and Brascoved) for facial prostheses under the pigmentation and chemical disinfection influence
Keywords: Initial deformation; Maxillofacial prosthesis; Permanent deformation